Bullying terhadap Kondisi Psikologis Anak Berdasarkan Kajian Qs. Al-Hujurat Ayat 11 - Nurazizah, Nurazizah; Nasokah, Nasokah; Khoiri, Ahmad (Institut Agama Islam Sumatera Barat Pariaman, 2022)
Bullying is a problem that is often found at the student level, even more so at the elementary school level. Not infrequently these phenomena can injure physically, psychologically, and morally both victims, perpetrators, and other communities. This background statement invites and reminds educators to analyze QS. Al-Hujurat verse 11. The objectives of this research are to: (1). knowing the effect of bullying on the psychological condition of children (2). knowing the relationship between Islamic education values ??and bullying with QS. Al-Hujurat Verse 11 (3). find out what efforts can be made to address bullying based on psychologists and the interpretation of the verses of bullying. This study uses library research and tahlily methods. The conclusions obtained from this study indicate that the effect of bullying makes it difficult for children to actualize themselves, especially in positive things. Anti-violence education and optimizing counseling guidance are efforts made by schools to overcome bullying behavior. In addition, mutual respect, love, and devotion to God which is the value of moral education contained in QS. Al-Hujurat verse 11 becomes the first reference in the development of children's character education